Informal Language in Academic Writing Analysis of Social Sciences PhD Dissertations in Pakistan - Parveen, Shahida; Hafeez, Muhammad Rashid (Pakistan Languages and Humanities Review, 2024)
This study was undertaken with a view to examine the patterns and prevalence of informal language in social sciences PhD dissertations in Pakistan. Formality in academic writing is essential for intelligibility. It eliminates any room for the author’s personal idiosyncrasies. Due to their systematic and formal structure, PhD dissertations are expected to adhere to the scholarly conventions and stylistic norms of the academic community. It explored a corpus of 15 most recent PhD dissertations from three social sciences disciplines. The dataset was taken from the disciplines that produced the highest number of PhD degrees in the past five years. The study employed the classification of informality proposed by Chang and Swales (1999), further modified by Hyland and Jiang (2017). The aim of the study was to identify deviations from these conventional norms and to explore various features of informality within the selected sample. Qualitative content analysis method was used for an in-depth analysis of the phenomenon. Markin Software 4 utilized for annotating the identified features of informality. The findings revealed that unattended anaphoric references were the most recurrent informal feature. These were followed by listing expressions and conjunctive adverbs/sentence-initial conjunctions. These findings show that actual linguistic practices contrast with conventional academic expectations.